Aerodynamic performance optimization of an airfoil-based airborne wind turbine using genetic algorithm. (15th July 2020) - Saleem, Arslan; Kim, Man-Hoe
Abstract: The present manuscript proposes an aerodynamically optimized airfoil-based-shell for performance enhancement of the buoyant airborne turbine system. An integrated code, based on a genetic algorithm, is developed to parametrize the asymmetric airfoil NACA-9415, analyse its aerodynamics and optimize the lift of the airfoil. The 3D steady-state analysis is performed on the optimized shell geometry with NREL-IV rotor using Reynolds Averaged Navier-Stokes (RANS) equation along with k − ω SST turbulence model. The performance of the airborne wind turbine with the optimized shell configuration is assessed in terms of aerodynamic coefficients including shell thrust coefficient, shell back pressure coefficient, turbine power coefficient and power augmentation ratio. The comparison of wind turbine performance with optimized and original NACA-9415 shell configuration demonstrates that shell optimization results in a maximum power coefficient of 1.25 and power augmentation ratio of 2.1 compared to the Betz limit. Highlights: Provide shell's effect on the aerodynamic performance of an airborne wind turbine. Optimize an airfoil based shell of an airborne wind turbine using genetic algorithm. Integrate airfoil parametrization method along with Xfoil into optimization code. The results showed a power augmentation with the optimized shell configuration.